Eristic Combat at Euthydemus 285e–286b. Issue 2 (3rd April 2019) - Jones, Russell E.; Sharma, Ravi
ABSTRACT: M.M. McCabe argues that in Plato's Euthydemus, Dionysodorus and Euthydemus hold a view she calls 'chopped logos' . Chopped logos implies that nothing said is false, or opposed to any other statement, or entailed by any other statement. We focus on a key piece of evidence for chopped logos, the argument concluding that there is no such thing as contradiction (285e9–286b6), and defend a competing interpretation. The argument in question, and the eristic exchanges as a whole, are simply examples of a dialectical game, a contest that is the verbal equivalent of physical competitions like wrestling or the pankration . The argument has no doctrinal significance and no deep connection with the other arguments of the dialogue. Its interest proves to be broadly methodological rather than doctrinal, a showpiece of eristic display.